Перспективні види та різновидності роду Juniperus L. для інтродукції у Лісостепу України - Kolodjazhenska, T.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The growth conditions of plants of the genus Juniperus L. in the areas of natural distribution are analyzed. The list of potentially promising species for the introduction trial in Forest-Steppe Ukraine is outlined (21 taxa). 75% of perspective species that have not found in the collections of botanical gardens and arboretum come from the Irano-Turanian floristic region.